2006
DOI: 10.1348/135910705x52516
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of motivational interviewing in physical health care settings

Abstract: While MI has high face validity across a number of domains in physical health care settings, the general quality of trials in this area is inadequate and therefore recommendations for its dissemination in this area cannot yet be made. More research into MI applied to health behaviour change is urgently required.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
144
1
18

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 216 publications
(165 citation statements)
references
References 28 publications
2
144
1
18
Order By: Relevance
“…It is, however, an approach that has been found to be efficacious in changing health behavior, as evidenced in several systematic reviews and meta-analyses (Armstrong et al, 2011;Knight, McGowan, Dickens, & Bundy, 2006;Lundahl & Burke, 2009;Lundahl et al, 2013;O'Halloran et al, 2014;Rubak, Sandbaek, Lauritzen, & Christensen, 2005;VanBuskirk & Loebach Wetherell, 2014). For example, a meta-analysis of 72 randomized controlled trials using MI in health related contexts revealed that it was more effective in improving both behavioral and health related outcomes relative to usual care in 80% of studies (Rubak et al, 2005).…”
Section: Isolating and Identifying MI Intervention Componentsmentioning
confidence: 99%
“…It is, however, an approach that has been found to be efficacious in changing health behavior, as evidenced in several systematic reviews and meta-analyses (Armstrong et al, 2011;Knight, McGowan, Dickens, & Bundy, 2006;Lundahl & Burke, 2009;Lundahl et al, 2013;O'Halloran et al, 2014;Rubak, Sandbaek, Lauritzen, & Christensen, 2005;VanBuskirk & Loebach Wetherell, 2014). For example, a meta-analysis of 72 randomized controlled trials using MI in health related contexts revealed that it was more effective in improving both behavioral and health related outcomes relative to usual care in 80% of studies (Rubak et al, 2005).…”
Section: Isolating and Identifying MI Intervention Componentsmentioning
confidence: 99%
“…17,21,93,94 Perhaps the best example of standardization of individually tailored processes is seen in motivational interviewing; the MI processes have been well described, standardized within a framework, widely disseminated, and demonstrated to be effective in many settings. 9,78,79,90,[95][96][97] Moreover, motivational interviewing has the advantage of several psychometrically sound program evaluation measures (eg, Motivational Interviewing Skills Code, 98 Motivational Interviewing Treatment Integrity 99 ) that can be used to ensure intervention integrity and assess intervention outcomes for common threats to validity. 9 While motivational interviewing uses only a subset of skills needed in health or wellness coaching, 80 it serves as an excellent example of how general processes that are used in highly individualized ways can be thoroughly described and well-validated.…”
Section: Individualized Vs Protocol-driven Coachingmentioning
confidence: 99%
“…Enhancing motivation. Diabetes management is dependent on patient motivation, and motivational interviewing (19) can be used to enhance motivation for diabetes self-care (73,74). This technique helps to identify and reinforce how important changing the behavior is to the patient and the benefits that the patient anticipates for making a change.…”
Section: Encouraging Realistic Expectationsmentioning
confidence: 99%